2020
DOI: 10.1155/2020/6157231
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Immobilization of the Upper Extremities on Spatiotemporal Gait Parameters during Walking in Stroke Patients: A Preliminary Study

Abstract: Background. The purpose of this study was to investigate the effects of upper extremity immobilization and consequent walking speed on spatiotemporal gait parameters in stroke patients with hemiparesis. Methods. The following variables were assessed or measured in 29 stroke patients: age, height, weight, disease duration, Korean version of the Mini-Mental State Examination (MMSE-K), Berg balance scale (BBS-K), functional gait assessment (FGA-K), cause of the disease (type of lesion), and hemiparetic side. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…This may suggest that the gait characteristics of sensory and non-sensory disorder balance dysfunction are different. Hong et al (2020) reported that the motor function of the hemiplegic lateral limbs in stroke-affected patients was impaired, and to maintain better gait stability during walking, the patient's step width was significantly increased and the stride length was reduced. However, the effect of non-sensory balance function on stroke-affected patients was not ruled out.…”
Section: Figurementioning
confidence: 99%
“…This may suggest that the gait characteristics of sensory and non-sensory disorder balance dysfunction are different. Hong et al (2020) reported that the motor function of the hemiplegic lateral limbs in stroke-affected patients was impaired, and to maintain better gait stability during walking, the patient's step width was significantly increased and the stride length was reduced. However, the effect of non-sensory balance function on stroke-affected patients was not ruled out.…”
Section: Figurementioning
confidence: 99%
“…In addition, arm cycling training improved post-stroke walking ability 11 and a coordination between the upper and contralateral lower limb during walking is demonstrated in post-stroke survivors 12 . Moreover, immobilization of the UE induced negative changes in spatial gait parameters 13 and the handgrip strength (part of UE function) was associated to walking in elderly 14 and patients with lumbar stenosis 15 . Since these studies suggest that the UE function affects the walking capacity, we expect that the UE function might also affect the 6MWT.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with hexapod robots, and those with even more limbs, quadruped robots have simpler structure and easy-to-establish motion models, so quadruped robots appear more frequently in scientific research and life [12]. The quadruped robot can adjust its movement gait according to different environments and different speeds [13]. The accessibility of the ground and the pitch of the ground slope will affect the quadruped robot's choice of gait, which leads to a variety of movements by the quadruped robot.…”
Section: Introductionmentioning
confidence: 99%